Study of sugar and tamarind addition on the quality of masin salted anchovy (stolephorus) - Chairul Anam Afgani; Ariskanopitasari Ariskanopitasari (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
Masin is a Sumbawanese traditional cuisine which is a sauce, made from mashed rebon shrimp, mixed with chilies, salt, flavorings, sugar and tamarind which fermented for 2 to 7 days. This study used anchovy as the basic material because of its abundant resources in West Nusa Tenggara. This study can be an opportunity for the development of processed anchovy. This study aimed to determine the effect of concentration of sugar and tamarind on the physical and organoleptic characteristics of anchovy. This research was conducted in a completely randomized design (CRD) with three replications of 2 factors such as the concentration of sugar and tamarind (0%, 0.6%, and 1.4%). Masin fermentation was carried out spontaneously for 7 days. The results showed that visually the anchovy masin did not grow fungi until the 14th day, except for samples with a concentration of sugar and tamarind 0.6% and 1.4%. Based on the L and oHue values, the anchovy masin has a reddish yellow color (yellow red) to yellow (yellow). Based on the results of the organoleptic test, it was found that the sugar concentration had an effect on texture and aroma, but did not affect color. The concentration of tamarind affected the aroma, but not the color and texture of masin.